(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the applicability and adverse effects of ozone therapy in Stomatology, through the analysis of some oral lesions. Method: This is a review with a qualitative approach with controlled primary studies, PICO question strategy and guiding question: is ozone therapy effective and safe in the treatment of oral lesions? The search for articles was performed on the virtual portals VHL, PubMed, Scielo, and the Cochrane Library. Results: 65 scientific productions were found, 32 were excluded, 32 were repeatedly indexed and 21 did not meet the inclusion criteria: complete articles published between 2000 and 2020, primary experimental and observational controlled studies with individuals with lichen planus, oral candidiasis and recurrent aphthous stomatitis or prosthetics who used ozone therapy for treatment. And the exclusion criteria: repeated indexed articles, studies of the gray literature, as they are productions not controlled by scientific or commercial editors, animal and in vitro tests, and case reports or series. In the end 11 articles were selected. Conclusions: Ozone in gaseous, aqueous or oily form promotes healing of the analyzed oral lesions without significant adverse effects.